Podcast sebagai Media Baru Dakwah di Era Digital - Azhima, Nur; Dita Puspito, Indra; Ariyanto, Budi; Sakinah, Nurul; Raning Tyas, Reka (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The expression of Islam on the Internet is becoming a new phenomenon of enthusiasm for religion in the future, people, especially the younger generation, prefer to use new media to gain religious knowledge, so digital da'wah is now a new demand and trend. Due to their flexibility and ability to be accessed on multiple platforms, podcasts are one of the most popular media today. The aim of this research is to determine and analyze the presence of podcasts as a new effective medium of da'wah in the digital era and to understand how this digital technology influences the communication process and its influence on society. The results of the research show that podcasts as a new medium of da'wah have great potential to have an impact positive in increasing religious understanding, strengthening moral values, and promoting peace and tranquility in society. This new media era is also marked by media convergence so that the emergence of interactive media now places audiences as consumers as well as producers of information. The presence of new media makes things easier for humans and the aspects of interactivity and connectivity with the characteristics contained in it